APPLICATION OF LEARNING VARIATIONS TO IMPROVE THE LEARNING OUTCOMES OF THE FOREHAND DRIVE TABLE TENNIS GAME IN CLASS STUDENTS VIII JUNIOR HIGH SCHOOL MUHAMMADIYAH 3 MEDAN ACADEMIC YEAR 2018/2019 - Keliat, Pedomanta (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna Medan, 2020)
This study aims to determine the increase in learning outcomes forehand drive table tennis drives in class VIII students of SMP Muhammadiyah 3 Medan Academic Year 2018/2019 through Learning Variations This research is a classroom action research. The study was conducted in two cycles, with data analysis techniques used in this study were descriptive based on qualitative analysis with the percentage: (1) From the test results of learning before using variations of learning obtained 27 students (90%) who have not reached the level of mastery learning , while 3 students (10%) have reached the level of mastery learning. Then learning is done using variations in learning (2) from the test of learning outcomes through learning variation in the first cycle obtained 14 students (46.67%) who reached the level of mastery learning, while 16 students (53.33%) have not reached the level of mastery learning. With an average value of 70.9. Then the learning variation (3) from the second learning achievement test in the second cycle contained 21 students (70%) who reached the level of mastery learning, while 9 students (30%) had not reached the level of mastery learning, with an average value of 8. Based on Data analysis can be said that through the variety of learning can improve learning outcomes in Table Tennis Forehand Drive in VIII grade students of Muhammadiyah Middle School 3 Medan Academic Year 2018/2019.